2014
DOI: 10.1097/dad.0000000000000029
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Primary Cutaneous Lymphoma With a γ/δ+ Phenotype and an Indolent Course

Abstract: Cutaneous [gamma]/[delta]+ T-cell lymphoma (CGD-TCL) is a rare but aggressive lymphoma associated with a poor prognosis in most patients. The clinicopathological spectrum is variable including predominantly epidermotropic infiltrates manifesting with patches and plaques or tumors with dermal and/or subcutaneous infiltrates. The diagnosis of CGD-TCL requires the demonstration of a [gamma]/[delta]+ phenotype by immunohistochemistry. We report 2 patients with epidermotropic cutaneous T-cell lymphomas displaying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…While the prognosis of CGD‐TCL is generally poor, indolent CGD‐TCL cases have also been reported . Particularly, MF‐like cases tended to have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…While the prognosis of CGD‐TCL is generally poor, indolent CGD‐TCL cases have also been reported . Particularly, MF‐like cases tended to have a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have identified numerous cases with epidermotropism. 10,11 In our meta-analysis, we found that nearly half of patients had some degree of epidermotropism in at least one of their biopsy specimens, and nearly a quarter presented with disease that was predominantly epidermotropic. For pathologists, this may dramatically shift the paradigm of the differential diagnosis of an epidermotropic T-cell infiltrate.…”
Section: Discussionmentioning
confidence: 79%
“…However, due to the publication of several series examining the survival of patients with epidermotropic disease in selected patients, this population may be enriched in our data set. This may be a strength of our report: given that several publications have collected epidermotropic cases with good survival outcomes, 10,11 our population should be enriched for patients with such patients, and we still do not detect a survival benefit to this phenotype. Rare clinical presentations (eg, eczema-like or ulcerated) may also be enriched in this population, although the overall trend of patients presenting with nodules or tumors with or without ulceration does hold true to previously published literature.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this particular subset, regardless of its likely heterogeneity, clinical presentation appears to be similar to the main, aggressive subset with nodules, indurated plaques, ulcers or blistering lesions ( 11 ) located mainly on the limbs and trunk but which may also affect the face ( 5 , 11 ) or display a widespread distribution. Interestingly Merrill et al ( 13 ) suggested that a predominantly epidermotropic pattern might be associated with a more favourable outcome, although most other reported cases of “indolent” PCGDTCL displayed a more usual predominant dermal and/or subcutaneous involvement as in our 2 patients, even though a sparse epidermotropism was occasionally observed in patient 2.…”
Section: Discussionmentioning
confidence: 90%